Pertumbuhan Gereja dan Pemberitaan Injil di Era Digital Sebagai Analisa Peluang dan Tantangan - Sambo, Ferdy; Manalu, Nixon (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to identify and discover the growth of the church and the proclamation of the Gospel in the digital era, as well as the opportunities and challenges currently faced by the church in reaching congregations in regional and international contexts. This study is a post-positivist qualitative study. The research method used is a post- positivist qualitative research method with a descriptive approach. Data collection used was bibliographic books and literature, surveys, and interviews as appropriate references. The subject of the study is church growth and the proclamation of the Gospel in the digital era. The object of the study is church growth and the proclamation of the Gospel in the digital era as an analysis of opportunities and challenges. The results of the study show that digital technology provides opportunities for the church to proclamation of the Gospel, covering 76% of the existing opportunities, 11% of the challenges of using technology in the digital era, and 13% of the demographic challenges, enabling it to reach congregations in regional and international contexts.